Survival impact and safety comparison of pirfenidone and nintedanib for idiopathic pulmonary fibrosis: A meta-analysis - Arshad, Hafiz Muhammad Ehsan; Ali, Faaz; Babar, Anas; Raza, Muhammad Zain; Maqsood, Musab; Ameer, Akmal (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background and aim: Idiopathic pulmonary fibrosis (IPF) is a severe restrictive lung disease affecting approximately 3 million people worldwide with two approved antifibrotics, nintedanib and pirfenidone, available for use. This review aims to compare their survival impact and safety profile.Methods: Two databases and two trial registers along with additional sources were searched for cohorts reporting IPF patients of any age or stage, receiving either pirfenidone or nintedanib. The Inverse-Variance and Mantel-Haenszel method along with either a fixed- or random-effects model was used for analysing survival and other dichotomous outcomes, respectively.Results: 23 cohorts were included. The pooled analysis showed that compared to pirfenidone, nintedanib group had similar survival (HR=1.12; 95%-CI:0.99-1.27; P=0.07), all-cause mortality (OR=1.11; 95%-CI:0.94-1.31; P=0.22), drug switches (OR=1.82; 95%-CI:0.69-4.78; P=0.22), and treatment discontinuations (OR=0.92; 95%-CI:0.60-1.41; P=0.70), higher odds of diarrhoea (OR=12.39; 95%-CI: 5.67-27.07; P